Phylogenetic Tree Analysis of the Cold-Hot Nature of Traditional Chinese Marine Medicine for Possible Anticancer Activity - Fu, Xianjun; Song, Xuxia; Li, Xuebo; Keng Wong, Keng Wong; Li, Jiaoyang; Zhang, Fengcong; Wang, Changyun; Wang, Zhenguo (Hindawi Publishing Corporation [Commercial Publisher], 2017)
Traditional Chinese Marine Medicine (TCMM) represents one of the medicinal resources for research and development of novel anticancer drugs. In this study, to investigate the presence of anticancer activity (AA) displayed by cold or hot nature of TCMM, we analyzed the association relationship and the distribution regularity of TCMMs with different nature (613 TCMMs originated from 1,091 species of marine organisms) via association rules mining and phylogenetic tree analysis. The screened association rules were collected from three taxonomy groups: (1) Bacteria superkingdom, Phaeophyceae class, Fucales order, Sargassaceae family, and Sargassum genus; (2) Viridiplantae kingdom, Streptophyta phylum, Malpighiales class, and Rhizophoraceae family; (3) Holothuroidea class, Aspidochirotida order, and Holothuria genus. Our analyses showed that TCMMs with closer taxonomic relationship weremore likely to possess anticancer bioactivity.We found that the cluster pattern ofmarine organisms with reported AA tended to cluster with cold nature TCMMs. Moreover, TCMMs with salty-cold nature demonstrated properties for softening hard mass and removing stasis to treat cancers, and species withinMetazoa orViridiplantae kingdomof cold natureweremore likely to contain AA properties.We propose that TCMMs from these marine groups may enable focused bioprospecting for discovery of novel anticancer drugs derived from marine bioresources.